Topics in Topological Graph Theory - Beineke, Lowell W. (Ed.); Wilson, Robin J. (Ed.) (Cambridge : University Press, 2009)
The use of topological ideas to explore various aspects of graph theory, and vice versa, is a fruitful area of research. There are links with other areas of mathematics, such as design theory and geometry, and increasingly with such areas as computer networks where symmetry is an important feature.
Part of: Encyclopedia of Mathematics and its Applications (189 books)
Keywords: Topological Graph Theory